Pengaruh Media Sosial Instagram dan Word of Mouth Terhadap Keputusan Pembelian Produk - Ningsih, Trans; Suginam, Suginam (Forum Kerjasama Pendidikan Tinggi, 2024)
This research aims to determine how much influence social media instagram and word of mouth have on purchasing decisions in Youneed Clothes product. The research method used is descriptive and quantitative with the data sources used are primary and secondary data from a sample of 75 customers with data collection techniques by distributing online questionnaires. The data analysis method used is multiple linear regression analysis, multiple correlation analysis, hypothesis testing and analysis of the coefficient of determination. Based on the results of the study obtained multiple linear regression equation Y = 2,943 + 0.687X1 + 0.184X2. Hypothesis testing using t test shows that the social media instagram variables studied have a positive and significant effect on purchasing decisions with statistical results for social media instagram variables known to be tcount (7.796) > ttable (1.99254) with a significant value of 0.000 < 0.05, for the word of mouth variable, it is known that the value of tcount (1.610) < ttable (1.99254) with a significant value of 0.112 > 0.05, so it is known that the word of mouth variable has no effect on the purchasing decision variable. Simultaneously (F test) the results obtained Fcount > Ftable (72.403>3.12) at a significant 0.000 <0.05. This means that the two independent variables of social media and word of mouth have a positive and significant effect on the dependent variable of purchasing decisions. Furthermore, looking at the contribution of the independent variable to the dependent variable seen from the coefficient of determination (R2) of 0.653 so that purchasing decisions can be explained by social media and word of mouth of 65.3% while the remaining 34.7% is influenced by other variables outside the scope of research that are not researched.